Propagation technique system for the production of banana planting materials - Suhaimi Othman; Yusuf Mohd Kamil (2015)
Small scale growers can diversify their income by not only cultivating banana but also as nursery propagators. They can reduce their capital by producing their own planting materials. UMK researchers have developed corm nursery technique (Corm-Tech) which help the small scale growers to mass propagate banana planting materials on-farm. Further research has been done where two components has been added into Corm-Tech which are Corm-shad and Corm-fert that help to improve the technique and also has developed a nursery propagation system (NUPSYS) so that the operation run mechanically and automatically. By doing that, multiple cycles of mass propagation of quality banana planting materials was achieved with the equivalent quality of tissue culture planting materials. Therefore, the combination of all technology has come out with a complete system called Propagation technique system (PROPA-TechSys) which eventually will help the small scale growers to produce more banana planting materials with more efficient and precision. Moreover, the system is a green technology, labour saving and cost-saving.